Remarks from AUN Executive Director - DHIRATHITI, Choltis (Institutional Knowledge at Singapore Management University, 2022)
Dr. Choltis Dhirathiti is a Lecturer in Politics at the Faculty of Political Science at Chulalongkorn University, Thailand. His services to the public sector involve thinking-skill trainings and public sector strategies. As Executive Director of the AUN, Dr Dhirathiti applies his experience in public sector strategies, policy consultancy and human resource development to the work of regional and multilateral cooperation among universities in Southeast Asia.